The standard deviation of life-length, retirement incentives, and optimal pension design - Aronsson, Thomas 1963-; Blomquist, Nils Sören 1948- (CESifo, 2010)
In this paper, we consider how the retirement age as well as a tax financed pension system ought to respond to a change in the standard deviation of the length of life. In a first best framework, where a benevolent government exercises perfect control over the individuals; labor supply and retirement-decisions, the results show that a decrease in the standard deviation of life-length leads to an increase in the optimal retirement age and vice versa, if the preferences for the number of years spent in retirement; are characterized by constant or decreasing absolute risk aversion. A similar result follows in a second best setting, where the government raises revenue via a proportional tax (or pension fee) to finance a lump-sum benefit per year spent in retirement. We consider two versions of this model, one with a mandatory retirement age decided upon by the government and the other where the retirement age is a private decision-variable. -- uncertain lifetime ; retirement ; pension system